PENGARUH WAKTU SPIN COATING TERHADAP STRUKTUR DAN SIFAT LISTRIK SEL SURYA PEWARNATERSENSITASI - Desi Susanthy (Department of Physics – Universitas Negeri Padang UNP, 2014)
Energy crisis that hit the world can be perceived by the people of Indonesia. Alternative solution to this problem needs to be done such as utilizing solar energy. Solar Cells Dyes sensitized is a device that converting solar energy to electrical energy by using the interaction of photons with the photosensitizer. Generally, the solar cell is composed of electrodes, dye, electrolyte, and semiconductors. In this research, Dye use mangosteen peel. The purpose of research is to determine the effect of film thickness on the electrical properties of the solar cell. Based on the results of measurements and data analysis, there are of research such as of spin coating. There are sereval result of research such as; first, varying thickness depending time of spin coating. Thickness of sample are 67.8 µm for 2 minutes, 66.1 µm for 4 minutes, 63.0 for 6 minutesand 59.6 µm for 8 minutes; second, absorbance value of dye with 338.17 nm wavelenght is 2.270; the last, the samples produce 20 µA current and 130 mV voltage for 67.8 µm film thickness, 500 µA and 213 mV for 66.1 µm, 18 µA and 15 mV for 63.0 µm and 12 µA current and 1.7 mV for 59.6 µm. Keywords: TiO2 thin film, method of spin coater, DSSC, natural dye, fotosentitizer.